The more gold - the more enantioselective: cyclohydroaminations of γ-allenyl sulfonamides with mono-, bis-, and trisphospholane gold(I) catalysts ; dedicated to Professor Peter Hofmann on the occasion of his 65th birthday - Rodríguez Broncano, Lara-Isabel; Roth, Torsten; Lloret Fillol, Julio; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2012)
A series of chiral mono-, di-, and trinuclear gold(I) complexes have been prepared and used as precatalysts in the asymmetric cyclohydroamination of N-protected γ-allenyl sulfonamides. The stereodirecting ligands were mono-, di-, and tridentate 2,5-diphenylphospholanes, which possessed C1, C2, and C3 symmetry, respectively, thereby rendering the catalytic sites in the di- and trinuclear complexes symmetry equivalent. The C3-symmetric trinuclear complex displayed the highest activity and enantioselectivity (up to 95 % ee), whilst its mono- and dinuclear counterparts exhibited considerably lower enantioselectivities and activities. A similar trend was observed in a series of mono-, di-, and trinuclear 2,5-dimethylphospholane gold(I) complexes. Aurophilic interactions were established from the solid-state structures of the trinuclear gold(I) complexes, thereby raising the question as to whether these secondary forces were responsible for the different catalytic behavior observed.